Effect of Vitamin D Supplementation on the Prognosis of Post-stroke Fatigue: A Retrospective Cohort Study - Wang, Long; Zhao, Xue-min; Wang, Fu-yu; Wu, Jun-Cang; Wang, Yu (Frontiers in Neurology, 2021)
Objectives: We aimed to evaluate the effect of vitamin D supplementation in PSF patients with vitamin D deficiency on fatigue symptoms and outcomes. Methods: Patients with primary acute ischemic stroke (AIS) were recruited consecutively from July, 2016 to June, 2018. PSF patients were screened out with the Fatigue Severity Scale (FSS) questionnaire, serum concentrations of 25-hydroxyvitamin D (25-(OH)-D) were assessed with enzyme-linked immunosorbent assay (ELISA), and neurological function were evaluated with FSS and mRS scoring criteria. PSF patients with vitamin D deficiency were divided into two groups: study group in which patients received vitamin D supplementation (cholecalciferol, 600IU/d) along with usual care, and control group in which patients received usual care alone. At the end of 1 and 3 months after treatment, all PSE patients accepted re-measurement of serum vitamin D and re-evaluation of fatigue and neurological function. Results: A total of 532 AIS patients were consecutively recruited to participate in this study. Patients without post-stroke fatigue, non vitamin D deficiency, pre-stroke fatigue or vitamin D supplementation were excluded from the study. In addition, patients who lost follow-up were also excluded. Finally, one hundred thirty nine out of 532 (26.1%) patients with PSF and vitamin D deficiency received vitamin D supplementation treatment. FSS score was significant lower in the study group than that in the control group at 1 month (t=-4.731, P<0.01) and 3 months (t=-7.937, P<0.01) after treatment. One month after treatment, mRS score in the study group was lower than that in the control group without statistical difference (t=-0.660, P>0.05). Whereas, mRS were significantly higher in the study group than that in control group at 3 months after treatment (t=-4.715, P<0.01). Conclusions: Our results indicated that vitamin D supplementation could improve fatigue symptoms and neurological outcomes in PSF patients with vitamin D deficiency. Subject to replication in other settings, randomized controlled trial (RCT) might be undertaken to validate the potential beneficial impact of vitamin D supplementation in post-stroke patients found to be vitamin D deficient.